VSTM2L protects prostate cancer cells against ferroptosis via inhibiting VDAC1 oligomerization and maintaining mitochondria homeostasis - Juan Yang; Xiao Lu; Jing-Lan Hao; Lan Li; Yong-Tong Ruan; Xue-Ni An; Qi-Lai Huang; Xiao-Ming Dong; Ping Gao (Nature Communications)
Abstract Ferroptosis is a form of iron-dependent programmed cell death, which is distinct from apoptosis, necrosis, and autophagy. Mitochondria play a critical role in initiating and amplifying ferroptosis in cancer cells. Voltage-Dependent Anion Channel 1 (VDAC1) embedded in the mitochondrial outer membrane, exerts roles in regulation of ferroptosis. However, the mechanisms of VDAC1 oligomerization in regulating ferroptosis are not well elucidated. Here, we identify that a VDAC1 binding protein V-Set and Transmembrane Domain Containing 2 Like (VSTM2L), mainly localized to mitochondria, is positively associated with prostate cancer (PCa) progression, and a key regulator of ferroptosis. Moreover, VSTM2L knockdown in PCa cells enhances the sensitivity of RSL3-induced ferroptosis. Mechanistically, VSTM2L forms complex with VDAC1 and hexokinase 2 (HK2), enhancing their binding affinity and preventing VDAC1 oligomerization, thereby inhibiting ferroptosis and maintaining mitochondria homeostasis in vitro and in vivo. Collectively, our findings reveal a pivotal role for mitochondria-localized VSTM2L in driving ferroptosis resistance and highlight its potential as a ferroptosis-inducing therapeutic target for the treatment of PCa.